Analysis of Pvama1 genes from China-Myanmar border reveals little regional genetic differentiation of Plasmodium vivax populations - Zhu, Xiaotong (Parasit Vectors, 2016)
BACKGROUND: With the premise of diminishing parasite genetic diversity following the reduction of malaria incidence, the analysis of polymorphic antigenic markers may provide important information about the impact of malaria control on local parasite populations. Here we evaluated the genetic diversity of Plasmodium vivax apical membrane antigen 1 (Pvama1) gene in a parasite population from the China-Myanmar border and compared it with global P. vivax populations. METHODS: We performed evolutionary analysis to examine the genetic diversity, natural selection, and population differentiation of 73 Pvama1 sequences acquired from the China-Myanmar border as well as 615 publically available Pvama1 sequences from seven global P. vivax populations. RESULTS: A total of 308 Pvama1 haplotypes were identified among the global P. vivax isolates. The overall nucleotide diversity of Pvama1 gene among the 73 China-Myanmar border parasite isolates was 0.008 with 41 haplotypes being identified (Hd = 0.958). Domain I (DI) harbored the majority (26/33) of the polymorphic sites. The McDonald Kreitman test showed a significant positive selection across the ectodomain and the DI of Pvama1. The fixation index (F (ST)) estimation between the China-Myanmar border, Thailand (0.01) and Myanmar (0.10) showed only slight geographical genetic differentiation. Notably, the Sal-I haplotype was not detected in any of the analyzed global isolates, whereas the Belem strain was restricted to the Thai population. The detected mutations are mapped outside the overlapped region of the predicted B-cell epitopes and intrinsically unstructured/disordered regions. CONCLUSIONS: This study revealed high levels of genetic diversity of Pvama1 in the P. vivax parasite population from the China-Myanmar border with DI displaying stronger diversifying selection than other domains. There were low levels of population subdivision among parasite populations from the Greater Mekong Subregion. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s13071-016-1899-1) contains supplementary material, which is available to authorized users.